Versatile Bottom-Up Approach to Nanostructured Functional Materials for Optoelectronic Applications - Giorgio Macchi; Francesco Meinardi; Patrizia Valsesia; Riccardo Tubino (International Journal of Photoenergy)
A versatile strategy to load ordered mesoporous silica-based materials with functional molecular building blocks in order to obtain host-guest systems exhibiting specific functions is described. Optical microscope examination of the obtained material confirms that the addition of a chromophoric moiety to the reaction mixture is not detrimental in achieving the desired macroscopic morphology of the silica particles. A micro-photoluminescence investigation of the obtained material gave strong evidence that both surfactant micelles and the porous oxide matrix preserve the spectral features of the included molecular species in a nonconventional chemical environment.